Assessing silencing ability of tRNA derived fragments in zebrafish - Fernandes, Noémia Rita Alves (2014)
Since their discovery, small non-coding RNAs (sncRNAs) have been implicated in several eukaryotic regulatory mechanisms, such as post-transcriptional gene silencing, chromatin regulation and germline development. Although miRNAs constitute the most studied class of sncRNAs, the advent of high-throughput sequencing technologies allowed the discovery of new classes of sncRNA molecules. Recently, novel sncRNAs derived from tRNAs (tRNA-derived fragments) have been identified, whose biogenesis and functions are not yet well defined. In the last years the RNA laboratory of the Aveiro University has also identified tRNA derived fragments (tRFs) in zebrafish. The abundance of two of these tRFs, namely tRF_3 and tRF_4, which derive from the tRNA 5’-portion – and the fact that both are conserved in vertebrates, processed by Dicer and exhibit some ability to associate with Argonaut proteins, suggest that these fragments represent a novel class of regulatory RNAs that have evolved early in vertebrates and may be involved in ancient mechanisms of genome regulation. Taking this information into account, in this thesis the silencing ability of both tRF_3 and tRF_4 was studied. In order to do that, experiments were performed with a dual reporter system, which allows for the analysis of target regulation by the endogenous molecule. This assay revealed that both fragments have silencing ability, although only tRF_4 has a region whose destabilization inhibits its silencing ability, similarly to miRNAs. Gene target computational predictions for tRF_4 were also performed. The results obtained are related with tRF_4 expression pattern. This thesis shows that tRFs in zebrafish have silencing ability and further studies are required in order to determine, experimentally, their molecular targets.